Remoção de antinutrientes de fontes protéicas vegetais para alimentação do jundiá (Rhamdia quelen) - Bergamin, Giovani Taffarel (2013)
With the expanding aquaculture activity, high quality ingredients for fish feeding are required. In order to prevent the risk of depending on fish meal, research institutions and the industry itself, have conducted studies to reduce the dependence of fish meal increasing the nutritional value of alternative feedstuffs. The objective of the study was to evaluate different methods of inactivation of antinutritional compounds on nutrient availability of plant protein sources for catfish. The work was divided into three parts: removal of antinutrients, growth trial, and digestibility experiment. In the first part, different chemical treatments for removal of phytic acid, total phenols and tannins in canola, soybean and sunflower meals were tested. The treatments were: acidified water (pH 1.0); ethanol PA + methanol PA; acidified ethanol PA (pH 1.0); ethanol + water PA 70:30 pH 1.0; acidified water + ethanol PA, used separatelly. Washing with pH 1,0 water, followed by washing in ethanol PA was the best alternative for removal of phytic acid, phenols and tannins of canola, sunflower and soybean meal. In the growth experiment were evaluated growth performance, body composition, biochemical parameters, enzymatic profile and intestinal morphometry of juvenile catfish fed with plant ingredients, treated or not treated for removal of antinutrients. Treatments were: control diet, with fish meal as only protein source (CON); replacement of 30% of fishmeal protein by untreated soybean meal (SNT), canola meal (CNT) and sunflower meal (GNT) or the same ingredients submitted to treatment: (ST), (CT) and (GT) (soybean, canola and sunflower, respectively). The treatment is effective, with the exception of phytic acid in soybean meal. ST and CT can replace 30% of fish meal protein, without affecting the growth of animals. There is no difference in the performance of fish fed CT compared to CNT, and GT compared to GNT. For soybean meal, there is improvement in the nutritional value after treatment. The biochemical changes do not appear to be linked to the antinutritional factors. There is no interference of the treatment on the enzymatic activity of silver catfish. Fish fed with untreated ingredients showed enlargement in the thickness of the muscle layer in the intestinal epithelium. The number of villi is higher in fish fed with treated ingredients. There is an increase in the thickness of the lamina propria of the villi in fish fed with the untreated ingredients. In the digestibility experiment, were evaluated the apparent digestibility coefficients (ADCs) of plant ingredients, submitted or not to chemical treatment to remove antinutritional factors in diets for jundiá. The ADC for crude protein was higher in ST, compared to CT and CNT, but did not differ from the others. GNT, GT and CNT showed the lowest ADC for organic matter. The removal of antinutrients do not affect the ADC of crude protein, dry matter and organic matter in soybean and sunflower meal. For canola meal, removing antinutritional factors improve dry matter digestibility. In addition, besides the antinutrients, special care must be taken to concentration or removal of other nutrients when using chemical treatments, otherwise the nutritional value of the ingredient can be affected.